Science and technology in modern China, 1880s-1940s - Tsu, Jing; Ellman, Benjamin A.; Amelung, Iwo (Brill, 2014)
Science and Technology in Modern China, 1880s-1940s looks at the transnational routes for the development of science and technology in the first pivotal decades of modern China.
Includes index. - Description based on print version record
Keywords: Electronic books; Aufsatzsammlung; Geschichte 1880-1949; Technik; Naturwissenschaften; China